APPLICATION OF TRIPLE-ENTRY BOOKKEEPING WITH BLOCKCHAIN TECHNOLOGY AS AN EFFORT TO PREVENT ACCOUNTING FRAUD - Budi Septiawan; Windi Fartika (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to find out how blockchain technology which is very popular in the world of cryptocurrencies can be applied to accounting as an effort to prevent accounting fraud. Where blockchain technology is packaged as a triple-entry recording system so that the level of security of recording transactions becomes more transparent and makes audit trails easier. The research method in this study is by descriptive and qualitative analysis methods, namely by collecting, presenting and analyzing the information / data obtained so that a fairly clear picture of the problem discussed can be obtained. The results of this study show that the application of triple-entry bookkeeping with blockchain technology offers the benefits of traceability, punctuality, protection against manipulation and high transparency. Triple-entry bookkeeping is a solution to solve transparency issues and fraud activity problems that have not been completely resolved so far.